Why We should Recommend Exercise in Pregnancy? - Manuela Filipec; Ratko Matijević (Clinical and Experimental Obstetrics & Gynecology, 2022)
Objective: This narrative review is presenting the impact of exercise on pregnant women and fetus and provides current recommendations for exercise in pregnancy. Mechanism: Exercise during pregnancy has a numerous effects on both pregnant woman and her fetus. When recommending exercise during pregnancy, it is necessary to keep in mind the physiological responses of the body’s systems during exercise, changes occuring in pregnancy and the influence of this changes on pregnant woman’s body as well as on the fetus and fetal responses to exercise during pregnancy. The type, intensity, duration, and frequency of exercise should be adjusted to the level of physical activity of pregnant women and period of pregnancy in order to achieve clinically significant health benefits. Findings in Brief: Exercise in pregnancy is beneficial for both the mother and her fetus and contributes to the prevention of pregnancy-related disorders. It is recommend to exercise 30 minutes daily five days a week with a tendency to increase the exercise each day in order to accumulate 150 to 300 minutes of exercise per week with moderate intensity. Conclusions: Regular exercise leads to specific adaptation processes of the body systems improving the physical and mental health of pregnant women with positive effect on her fetus.